Genetic polymorphisms of pharmacogenomic VIP variants in the Dai population from Yunnan province. Issue 7 (29th April 2020) - Cheng, Yujing; Dai, Run; Chen, Wanlu; Li, Qi; Zhang, Chan; Yang, Tonghua
Abstract: Background: Pharmacogenomics plays a crucial role in individualized therapy, but the variant information of pharmacogenomics in the Dai population is limited. We therefore aimed to screen very important pharmacogenetic (VIP) in the Dai population and compared differences between Dai and other 25 populations. Methods: In this study, we genotyped 73 VIP variants from the PharmGKB and compared genotype distribution of variants in Dai with other 25 populations by χ2 test. To assess the genetic relationship among 26 populations, we performed the structure analysis. In addition, pair‐wise F‐statistics (Fst) was calculated to measure the population differentiation. Results: We found 12, 10, 13, 17, 11, 39, 46, 46, 45, 43, 49, 46, 46, 46, 49, 45, 41, 42, 48, 53, 45, 50, 50, 51, 47, and 50 significantly different variants in Dai compared with other 25 populations. Genetic structure analysis showed Dai had close relationships with CDX (Chinese Dai in Xishuangbanna), CHB (Han Chinese in Beijing), JPT (Japanese in Tokyo), and KHV (Kinh in Ho Chi Minh City, Vietnam). Moreover, Dai is the most similar to KHV according to Fst analysis. Conclusions: Our study complement the pharmacogenomics information of Dai population from Yunnan province and provide a theoretical basis for personalized medicine.